How can the integration of renewable energy and power-to-gas benefit industrial facilities? From techno-economic, policy, and environmental assessment. (16th October 2020) - Preston, Nicholas; Maroufmashat, Azadeh; Riaz, Hassan; Barbouti, Sami; Mukherjee, Ushnik; Tang, Peter; Wang, Javan; Haghi, Ehsan; Elkamel, Ali; Fowler, Michael
Abstract: This paper applies a mixed integer linear programming model developed in GAMS to simulate the integration of Power-to-Gas infrastructure into an industrial manufacturer's energy system subject to the existing thermal and electrical energy demands, as well as a third hydrogen energy profile. This work is novel in that it assesses the challenges and economic incentives available to make feasible the installation of a hydrogen-based energy storage systems within the Province of Ontario from a techno-economic, policy and environmental perspectives. The energy hub analyzed in this work uses electricity from the power grid and solar PVs to meet the manufacturer's demands, while converting the excess to hydrogen gas, which is used across an array of pathways to generate revenue. ThisThis includes a blend ofof hydrogen for fuel cell vehicles (FCVs), hydrogen for forklifts, and the direct injection of hydrogen into the facility's natural gas, adding renewable content to the heating, and manufacturing processes. Our primary objective was to implement a safe design that minimizes capital and operating costs, resulting in a favorable business case for producing hydrogen, and providing ancillary grid services. However, Power-to-Gas creates a net-emission reduction that can be used not only to sell emission allowances in the provincial carboncarbon tax program for up to $30/t-CO2eq but to assist the Company in achieving their strategic emission reduction targets. Installation of the selected Power-to-Gas system would require a total capital investment of $2, 620, 448 with the electrolyzers and solar panels accounting for 41% and 17% of the capital costs, respectively. The compressors will account for most of the operating costs which total $237, 653 annually. Within the energy hub, 76, 073 kg-H2 has been produced per year for end-use applications. A sensitivity analysis was performed by varying both hydrogen and carbon credit price which predicted a potentialpotential CO2 offset of 2359.7 tonne/yr with a payback period of as little as 2.8 years. Highlights: MILP model optimizing an industrial energy system incorporating new P2G technology. Costing of a P2G installation and analysis of ROI based on hydrogen revenue streams. A sensitivity analysis based on environmental and regulatory policy changes. Determines emission offsets resulting from the use of fuel cell vehicles. A policy review of the challenges of implementing P2G in Ontario.